Ten cents a dance - Fletcher, Christine, 1964- (New York : Bloomsbury, 2008)
In 1941 Chicago, fifteen-year-old Ruby, a Polish-American girl from the slums, leaves her meat-packing plant job to be a "taxi" dancer, paid a dime apiece to dance with men in a dance hall, and becomes entangled with the mob.
Booklist.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Dance -- Juvenile fiction; Families -- Illinois -- Chicago -- Juvenile fiction; Nightclubs -- Juvenile fiction; Poverty -- Juvenile fiction; World War, 1939-1945 -- Juvenile fiction; Conduct of life -- Fiction; Dance -- Fiction; Family life -- Illinois -- Chicago -- Fiction; Historical fiction; Nightclubs -- Fiction; Poverty -- Fiction; World War, 1939-1945 -- Fiction; Conduct of life -- Fiction; Dance -- Fiction; Family life -- Chicago (Ill.) -- Fiction; Historical fiction; Nightclubs -- Fiction; Poverty -- Fiction; World War, 1939-1945 -- Fiction; Chicago (Ill.) -- History -- 20th century -- Juvenile fiction; Chicago (Ill.) -- History -- Fiction; Chicago (Ill.) -- History -- Fiction